Present Status on the Use of Anabolic Steroids and Feed Additives in Small Scale Cattle Fattening in Bangladesh - Islam, MH; Hashem, MA; Hossain, MM; Islam, MS; Rana, MS; Habibullah, M (Progressive Agriculture, 2013)
This study was conducted to find out the relationship among different aspects of cattle fattening and use of anabolic steroids and feed additives. The data were collected through an interview schedule from 150 respondents of 6 upazila of 3 districts who were involved in small scale cattle fattening. Parameters were studied in relation to socio-economic conditions of farmers and use of anabolic steroids and feed additives and their effects on animals and environment. In this study 72% farmers' were involved in agriculture, followed by 23.3% in livestock business. About 46% farmers had primary education, 10.7% had higher secondary school certificates, 5% obtained above higher secondary education and the rest of them were illiterate. Irrespective of literacy only 9.3% of the farmer had training. About 89.3% respondents used their own labors, 7.3% dependent on hired labor and the rest 3.3% get labour from both sources. Results showed that about 58% respondents used anabolic steroids for the duration of 3 to 6 months long cattle fattening (P<0.001) program. The chi-square (14.09) value of annual income indicates that with increase of annual income, use of anabolic steroids have decreased. The significant (P<0.01) association was observed in case of anabolic steroids and source of money, annual income, number of cattle fattening, breeds, fattening period, starting and finishing age. The rs value of annual income, source of money, starting and finishing age were positively correlated with feed additives. About 78% respondents used feed additives for cattle fattening from own resources (P<0.001) and most of cattle fattened for 3 to 6 months (P<0.01). The result demonstrated that respondents of low annual income used more anabolic steroid and feed additives as a growth promoter for cattle fattening and they prefer in powder form. DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16553 Progress. Agric. 23(1 & 2): 1 13, 2012